Pengaruh Permainan Maze Alphabet Terhadap Keaksaraan Awal Anak Usia 5-6 Tahun - Asih Budi Kurniawati; Nursabilla Maharani Dwiyanvi; Devi Nawangsasi (Jambura Early Childhood Education Journal, 2026)
This study was motivated by the low early literacy skills of children aged 5-6 years who were located at PAUD Raudhatul Jinan Bandar Lampung. This study aims to determine the effect of the alphabet maze game on the early literacy of children aged 5-6 years. This study is a quantitative study with a Quasi Experiment research method and a Nonequivalent Control Group Design research design, namely with one experimental class and one control class. The sample of this study was children aged 5-6 years at PAUD Raudhatul Jinan totaling 50 children. The data collection technique used observation techniques in the form of checklists and documentation. The data analysis technique in this study used a simple linear regression analysis test. The results of the simple linear regression analysis test showed a significant value = 0.000 ˂ 0.05, so Ha was accepted, which means that there is an effect of the use of the alphabet maze game on the early literacy of children aged 5-6 years in group B PAUD Raudhatul Jinan Bandar Lampung